Inflectional classes in Kipsigis - Maria Kouneli (Glossa, 2022)
In this paper, I provide a description and analysis of conjugation classes in Kipsigis (Nilotic; Kenya). While traditional descriptions discuss two conjugation classes, I show that the morphophonological properties of Class II can be reduced to the presence of a moraic affix spelling out a verbalizing head (little v in theories like DM). On the semantic side, I show that Class II is primarily used for causative verbs, and I identify the verbalizing head as vCAUSE. The analysis highlights three properties of inflectional classes that are relevant for their analysis cross-linguistically: i) there is a close (historical or synchronic) connection between conjugation classes and transitivity, ii) what looks like a conjugation class can be reduced to the spellout of a verbalizing head, iii) there is an asymmetry between nouns and verbs for a number of languages: verbs tend to have fewer inflectional classes than nouns. Finally, the analysis of the Kipsigis facts contributes to a growing body of literature on mora affixation in Nilotic and beyond (e.g., Trommer & Zimmermann 2014), and it shows that such abstract representations in combination with regular phonology are sufficient to derive apparently complex morphophonological alternations.